The Meaning of Causative Verbs - Karimjonova Shahlo Ravshanjonovna (Jurnal Multidisiplin Madani, 2023)
In this article the author analyzed the background of causation in linguocognitive aspect. The author compared causative verbs in two languages by translating sentences from English to Uzbek